IDDF2019-ABS-0126 Levofloxacin sequential therapy versus bismuth quadruple therapy in the second-line and third-line treatment of helicobacter pylori -a multicenter randomized trial. (7th June 2019) - Liou, Jyh-Ming; Chen, Po-Yueh; Chen, Chieh-Chang; Fang, Yu-Jen; Bair, Ming-Jong; Lin, Jaw-Town; Wu, Ming-Shiang
Abstract : Background: We aimed to compare the efficacy and safety of 14-day levofloxacin sequential therapy versus 10-day bismuth quadruple therapy in the second-line and third-line treatment of Helicobacter pylori (H. pylori) infection. Methods: H. pylori infected patients who failed after one treatment were eligible in this open-labeled, multicenter, randomized trial, and were randomized to receive (1) levofloxacin sequential therapy (EAML ): esomeprazole 40 mg and amoxicillin 1 g for the first 7 days, followed by esomeprazole 40 mg, metronidazole 500 mg, and levofloxacin 250 mg for another 7 days (all twice daily); or (2) bismuth quadruple therapy (BQ ) : esomeprazole 40 mg twice daily, bismuth tripotassium dicitrate 300 mg four times a day, tetracycline 500 mg four times a day, and metronidazole 500 mg three times a day, for 10 days. The primary end point was the eradication rate in the second-line treatment according to intention to treat (ITT) analysis. The minimum inhibitory concentrations were determined by agar dilution test. Results: A total of 560 patients have been recruited and results were available for analysis in 533 patients up to Jan 2019. The demographic characteristics and antibiotic resistance rates were similar across the two treatment groups. The eradication rate in the second line treatment was 88.3% (235/266) and 88.4% (236/267) in the levofloxacin sequential therapy and bismuth quadruple therapy groups, respectively (p=1.000) in the ITT analysis. The eradication rates were 89.7% (235/262) and 92.9% (236/254) in the levofloxacin sequential therapy and bismuth quadruple therapy according to PP analyses, respectively (p=0.195). The efficacy of levofloxacin sequential therapy, but not bismuth quadruple therapy, appeared to be affected by levofloxacin resistance. The frequency of any adverse effects was higher in patients treated with bismuth quadruple therapy than levofloxacin sequential therapy (76.4% vs. 44.1%, p<0.001). The efficacy of bismuth quadruple therapy and levofloxacin sequential therapy in the third-line treatment were 70.6% (12/17) and 63.6%(7/11), respectively. (table 1 ) Conclusions: Levofloxacin sequential therapy and bismuth quadruple therapy are similarly effective in the second-line treatment for H. pylori infection. (Trial registration number: NCT NCT03148366 )